Receptor Tyrosine Kinases and Inhibitors in Lung Cancer - Evan Pisick; Simha Jagadeesh; Ravi Salgia (The Scientific World Journal)
Lung cancer is a deadly disease with high mortality and morbidity. Most cases of lung cancer are due to non-small cell carcinoma, with 16% of cases being small cell carcinoma. The biology at a cellular level is of interest at many levels. Knowing cellular pathways helps to further enhance our knowledge of how lung cancer cells survive, proliferate, and metastasize. The receptor tyrosine kinases (RTKs) located at the cellular membrane are becoming of great interest as sites for targeted therapies for lung cancers. This review will discuss the RTKs that are involved in lung cancers and the newer therapies that are being tested. We will specifically discuss receptors such as epidermal growth factor receptor, c-Kit receptor, VEGF receptor, c-Met receptor, insulin growth factor receptor, and Eph receptor. The inhibitors against the specific RTKs are in various preclinical and clinical trials, and this will be detailed.